Natural Variation within a Species for Traits Underpinning C4 Photosynthesis. Issue 2 (20th April 2018) - Reeves, Gregory; Singh, Pallavi; Rossberg, Timo A.; Sogbohossou, E.O. Deedi; Schranz, M. Eric; Hibberd, Julian M.
Abstract : The C4 species Gynandropsis gynandra exhibits natural variation in traits important for C4 photosynthesis. Abstract: Engineering C4 photosynthesis into C3 crops could substantially increase their yield by alleviating photorespiratory losses. This objective is challenging because the C4 pathway involves complex modifications to the biochemistry, cell biology, and anatomy of leaves. Forward genetics has provided limited insight into the mechanistic basis of these properties, and there have been no reports of significant quantitative intraspecific variation of C4 attributes that would allow trait mapping. Here, we show that accessions of the C4 species Gynandropsis gynandra collected from locations across Africa and Asia exhibit natural variation in key characteristics of C4 photosynthesis. Variable traits include bundle sheath size and vein density, gas-exchange parameters, and carbon isotope discrimination associated with the C4 state. The abundance of transcripts encoding core enzymes of the C4 cycle also showed significant variation. Traits relating to water use showed more quantitative variation than those associated with carbon assimilation. We propose that variation in these traits likely adapted the hydraulic system for increased water use efficiency rather than improving carbon fixation, indicating that selection pressure may drive C4 diversity in G. gynandra by modifying water use rather than photosynthesis. The accessions analyzed can be easily crossed and produce fertile offspring. Our findings, therefore, indicate that natural variation within this C4 species is sufficiently large to allow genetic mapping of key C4 traits and regulators.